Foundations of Implementation of Risk Management Process within Project Management - Kampova, Katarina (Communications - Scientific letters of the University of Zilina, 2011)
Nowadays, most organisations are experiencing unprecedented levels of change. Change has become a way of life for organisations that need to remain effective and competitive in order to thrive. It is essential to manage the inherent risk associated with change and innovation. Project brings together resources, skills, technology and ideas to deliver business benefits or to achieve business objectives. Good project management helps to ensure that these benefits or objectives are achieved within budget, within time and to the required quality. Project management must control and contain risks if a project is to stand a chance of being successful and ensure the security of the project. Without an ongoing and effective risk management procedure it is not possible to give confidence that the project is able to meet its objectives. This paper covers the main aspects of the management of risk as they apply to project management and proposes the methodology, which is applicable in implementation of risk management within a project.